Mathematical methods in engineering and applied sciences - Dutta, Hemen, 1981- (Boca Raton : CRC Press, 2020)
"This book covers tools and techniques used for developing mathematical methods and modelling related to real-life situations. It brings forward significant aspects of mathematical research by using different mathematical methods such as analytical, computational, and numerical with relevance or applications in engineering and applied sciences. Presents theory, methods, and applications in a balanced manner Includes the basic developments with full details Contains the most recent advances and offers enough references for further study Written in a self-contained style and provides proof of necessary results Offers research problems to help early career researchers prepare research proposals "Mathematical Methods in Engineering and Applied Sciences" makes available for the audience, several relevant topics in one place necessary for crucial understanding of research problems of an applied nature. This should attract the attention of general readers, mathematicians, and engineers interested in new tools and techniques required for developing more accurate mathematical methods and modelling corresponding to real-life situations"--
OCLC-licensed vendor bibliographic record.
Keywords: Engineering mathematics; TECHNOLOGY / Operations Research; MATHEMATICS / Applied